2015
DOI: 10.3892/ol.2015.3308
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of 31 cases of refractory acute promyelocytic leukemia treated with compound realgar natural indigo tablets administered alternately with chemotherapy

Abstract: Abstract. The aim of the present study was to investigate the long-term survival of patients with refractory acute promyelocytic leukemia (APL) that were administered alternately with compound realgar natural indigo tablet (CRNIT) treatment and chemotherapy. In total, 31 patients with refractory APL were administered with CRNIT treatment alternately with chemotherapy. The complete remission (CR) and relapse rates were estimated by bone marrow (BM) examination. The expression of the promyelocytic leukemia-retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
8
1
2
Order By: Relevance
“…As 2 S 2 , which shows similar efficacy and fewer adverse effects (14,15), is much less toxic than arsenic trioxide and other common arsenic compounds, including sodium arsenite and arsenate (14,38), and has been considered as an alternative oral arsenic agent for cancer treatment. In China, As 2 S 2 has already been approved for clinical use in the treatment of leukemia (16)(17)(18)39). A series of clinical studies and trials proved that treatment with As 2 S 2 was well tolerated, with only moderate side-effects in patients suffering from APL (13,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As 2 S 2 , which shows similar efficacy and fewer adverse effects (14,15), is much less toxic than arsenic trioxide and other common arsenic compounds, including sodium arsenite and arsenate (14,38), and has been considered as an alternative oral arsenic agent for cancer treatment. In China, As 2 S 2 has already been approved for clinical use in the treatment of leukemia (16)(17)(18)39). A series of clinical studies and trials proved that treatment with As 2 S 2 was well tolerated, with only moderate side-effects in patients suffering from APL (13,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic disulfide (As 2 S 2 ), as the predominant active ingredient of realgar, also known as 'Xiong-Huang' in traditional Chinese medicine, is considered to be a candidate for the treatment of several types of malignancies; it exhibits relatively low toxicity, and has the advantage of being orally administered (10,(13)(14)(15). A series of basic and clinical studies have reported the antitumor effects of As 2 S 2 in different types of malignancies, particularly hematopoietic tumors such as APL (13,(16)(17)(18)(19). Recently, there is increasing evidence to support that As 2 S 2 has the ability to induce apoptosis and inhibit the growth of hematopoietic and solid tumor cell lines, such as human lymphoma cell lines (20), cervical cancer cell lines (21), human hepatocellular carcinoma cells (22), and human osteosarcoma cell lines (23).…”
Section: Arsenic Disulfide-induced Apoptosis and Its Potential Mechanmentioning
confidence: 99%
“…Arsenic disulfide (As 2 S 2 ) is an orange-red crystalline mineral and the principal effective component of realgar, and has been used extensively to treat various diseases in ancient China and Europe ( 1 ). In recent decades, a series of studies have revealed the marked therapeutic potential of As 2 S 2 in hematopoietic tumors, particularly acute promyelocytic leukemia (APL) ( 2 4 ). In addition, recent evidence has revealed the potent anticancer effect of As 2 S 2 against various human solid cancer cell lines, but with markedly decreased toxicity in normal somatic cells ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that pirarubicin-based treatment regimen may have less toxic and side effects and higher safety in AML patients. Mitoxantrone is found to have a higher response rate to AML at a high dose, but it also leads to decrease in EF, increase in Tei index, and significant decrease in GLS and GCS, as well as higher E/E ratio and lower E/A ratio, which show that the ventricular diastolic ability is also damaged (31). Other studies found that mitoxantrone also causes leukopenia, erythropenia and thrombocytopenia in blood, and even treatment-related acute leukemia in the treatment of patients with multiple sclerosis (32).…”
Section: Discussionmentioning
confidence: 99%